Core/Whole Genome Multilocus Sequence Typing and Core Genome SNP-Based Typing of OXA-48-Producing Klebsiella pneumoniae Clinical Isolates From Spain - Miro, Elisenda; Rossen, John W. A.; Chlebowicz, Monika A.; Harmsen, Dag; Brisse, Sylvain; Passet, Virginie; Navarro, Ferran; Friedrich, Alex W.; García-Cobos, S. (Frontiers in Microbiology, 2020)
Whole-genome sequencing (WGS)-based typing methods have emerged as promising and highly discriminative epidemiological tools. In this study, we combined gene-by-gene allele calling and core genome Single Nucleotide Polymorphism (cgSNP) approaches to investigate the genetic relatedness of a well-characterized collection of OXA-48-producing K. pneumoniae isolates. We included isolates from the predominant sequence type ST405 (n=31) OXA-48-producing K. pneumoniae clone and isolates from ST101 (n=3), ST14 (n=1), ST17 (n=1) and ST1233 (n=1), obtained from eight Catalan hospitals. Core-genome multilocus sequence typing (cgMLST) schemes from Institut Pasteur’s BIGSdb-Kp (634 genes) and SeqSphere+ (2,365 genes), and a SeqSphere+ whole-genome MLST (wgMLST) scheme (4,891 genes) were used. Allele differences or allelic mismatches and the genetic distance, as proportion of allele differences, were used to interpret the results from a gene-by-gene approach, whereas the number of SNPs was used for the cgSNP analysis. We observed between 0-10 and 0-14 allele differences among the predominant ST405 using cgMLST and wgMLST from SeqSphere+, respectively; and < 2 allelic mismatches when using Institut Pasteur’s BIGSdb-Kp cgMLST scheme. For ST101, we observed 14 and 54 allele differences when using cgMLST and wgMLST SeqSphere+, respectively; and 2-5 allelic mismatches for BIGSdb-Kp cgMLST. A low genetic distance (<0.0035, a previously established threshold for epidemiological link) was generally in concordance with a low number of allele differences (<8) when using the SeqSphere+ cgMLST scheme. The cgSNP analysis showed 6 to 29 SNPs in isolates with identical allelic SeqSphere+ cgMLST profiles and 16 to 61 cgSNPs among ST405 isolates. Furthermore, comparison of WGS-based typing results with previously obtained MLST and pulsed-field gel electrophoresis (PFGE) data showed some differences, demonstrating the different molecular principle underlying these techniques. In conclusion, the use of the different WGS-based typing methods that were used to elucidate the genetic relatedness of clonal OXA-48-producing K. pneumoniae all led to the same conclusions. Furthermore, threshold parameters in WGS-based typing methods should be applied with caution and should be used in combination with clinical epidemiological data and population and species characteristics.